The mortality factor of rafflesia buds (Rafflesia tuan-mudae) in Sungai Betung Distric, Bengkayang Regency - Herlina Darwati; Noviana Azahra; Destiana (Global Forest Journal, 2025)
The death of the Rafflesia tuan-mudae buds can be caused by the environmental conditions of the growing place and the host R. tuan-mudae. The purpose of this study is to describe the habitat conditions of R. tuan-mudae and found the cause of the death of Bud R. tuan-mudae. The study used a survey method with data collection techniques in the form of a double plot that is placed purposively where R. tuan-mudae is found with a size of 20 m × 20 m. Based on the result of the study R. tuan mudae was found in 3 observation plots, the first is found in Bukit Salapar, and the other plot is in Gunung Bawang Raya. The results of measurements of the environmental conditions of the R. tuan-mudae habitat show that R. tuan-mudae is often found in conditions of air humidity 87.4 – 91 %, air temperature 25.7 – 26.7℃, soil pH 4.1 – 4.2, soil moisture 69 – 70 %, soil temperature 25 – 26℃, light intensity 542 – 1782 lux, land slope 52.8 – 64.0% and altitude 292-537 MASL. The condition of R. tuan-mudae population has a percentage of 32% live buds, 60% of dead buds and 8% die after blooming. The death of R. tuan-mudae buds is caused by high air humidity 91%, host death, a very steep land slope 64.0% and buried by litter.